Living arrangements, health lifestyles, and health outcomes among Chinese oldest-old - Wang, Jie; Zhang, Lanxi; Wang, Shen; Zhang, Li (Frontiers in Public Health, 2023)
Background Prior literature has documented a strong correlation between living arrangements and older adults' health outcomes. However, few studies have explained why this association exists. This study took the health lifestyle theory approach and brought health lifestyles into the link between living arrangements and Chinese oldest-old health outcomes. It examined (1) whether healthy lifestyle behaviors among the oldest-old varied by household contexts and (2) whether the health disparities among the Chinese oldest-old in different household contexts could be partially explained by their healthy lifestyles. Methods Using the most recent 2018 data released by the Chinese Longitudinal Healthy Longevity Survey (CLHLS), latent class analysis was applied to identify predominant health lifestyles among the Chinese oldest-old aged 85-105 years. Regression analyses were used to test the mediating effect of health lifestyles. Results Three distinct classes representing the health lifestyles of Chinese oldest-old emerged; health lifestyle patterns were found to vary by elders' living arrangements. The respondent's health lifestyles in diverse residential structures served as a mediator which can partially explain the health disparities among the oldest-old. Conclusion The results suggested that health lifestyles can serve as a mediator to explain the association between oldest-old living arrangement patterns and their health outcomes. The findings highlighted the importance of family, lifestyles, and cultural contexts to the health of the oldest-old.